2017
DOI: 10.1002/pros.23441
|View full text |Cite
|
Sign up to set email alerts
|

Milk and other dairy foods in relation to prostate cancer recurrence: Data from the cancer of the prostate strategic urologic research endeavor (CaPSURE™)

Abstract: Background High‐fat dairy, particularly whole milk, in healthy men may increase risk of aggressive prostate cancer. However, data are limited regarding dairy after prostate cancer diagnosis. Method We conducted a prospective study among 1334 men with non‐metastatic prostate cancer in the Cancer of the Prostate Strategic Urologic Research Endeavor. Men answered a food frequency questionnaire in 2004‐2005 (median 2 years after diagnosis) and were followed until 2016 for recurrence, defined as: prostate cancer de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 41 publications
(75 reference statements)
1
30
1
Order By: Relevance
“…A meta-analysis of 12 prospective studies reported an increased risk of PCa among men who consumed large amounts of dairy products (RR = 1.11, 95% CI = 1.00-1.22) and calcium (RR = 1.39, 95% CI = 1.09-1.77) [52], whereas another meta-analysis of 45 studies reported no association between consumption of dairy products and PCa (RR = 1.06, 95% CI = 0.92-1.22) [53]. Moreover, several clinical studies reported a positive association between high-fat milk intake and PCa progression and no association with low-fat milk intake [54,55], and a positive association between calcium overdose and the risk of PCa was reported [52,56,57]. Furthermore, an animal study using a mouse PCa model reported that high milk consumption exhibited slight protective effects against PCa progression by decreasing the expression of Ki-67 and G protein-coupled receptor family C group 6 member A [58].…”
Section: Proteinmentioning
confidence: 99%
“…A meta-analysis of 12 prospective studies reported an increased risk of PCa among men who consumed large amounts of dairy products (RR = 1.11, 95% CI = 1.00-1.22) and calcium (RR = 1.39, 95% CI = 1.09-1.77) [52], whereas another meta-analysis of 45 studies reported no association between consumption of dairy products and PCa (RR = 1.06, 95% CI = 0.92-1.22) [53]. Moreover, several clinical studies reported a positive association between high-fat milk intake and PCa progression and no association with low-fat milk intake [54,55], and a positive association between calcium overdose and the risk of PCa was reported [52,56,57]. Furthermore, an animal study using a mouse PCa model reported that high milk consumption exhibited slight protective effects against PCa progression by decreasing the expression of Ki-67 and G protein-coupled receptor family C group 6 member A [58].…”
Section: Proteinmentioning
confidence: 99%
“…Pettersson et al [284] showed that men with the highest versus lowest intake of whole milk were at an increased risk of PCa progression. A prospective study among 1334 men with non-metastatic PCa in the Cancer of the Prostate Strategic Urologic Research Endeavor (CaPSURE ™ ) reported that whole milk consumption after PCa diagnosis was associated with increased risk of recurrence, particularly among very overweight or obese men [285]. Milk fat contains branched-chain fatty acids, whose metabolism is disturbed in PCa patients.…”
Section: Prostate Cancermentioning
confidence: 99%
“…Branched-chain fatty acids in milk and dairy products markedly enhance AMACR expression in PCa cells in vitro [289]. In contrast to whole milk, total dairy and fermented milk products did not correlate with PCa risk [281][282][283][284][285]. Milk fat and calcium are obviously not the primary causative nutritional factors in whole milk for PCa initiation and progression, as milk fat is abundant in cheese and other fermented milk products.…”
Section: Prostate Cancermentioning
confidence: 99%
“…A study by Torfadottir (13) reported increased risk for prostate cancer in Icelandic men who consumed more dairy products in adolescence, but, interestingly, no such correlation was found between consumption of dairy products in adult life and prostate cancer risk, highlighting the potential importance of adolescent exposure to sex steroids from milk. Milk consumption has also been associated with prostate cancer recurrence especially in obese men (66) and progression of cancer growth and increased mortality in patients with localized prostate cancer (14,67). In a recent meta-analysis, Aune et al (68) also found an increased risk for prostate cancer in men with higher intake of dairy products.…”
Section: Milk Consumption and Prostate Cancermentioning
confidence: 99%